The Influence of Failover on Software-Defined Network and Conventional Network - Saputra, Riffat Hasan; Subardono, Alif (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2020)
The growing use of the Internet resulted in the number of agencies that use two or more internet gateway paths or so-called Internet Service Providers (ISPs) to maintain network availability. Using two or more gateway paths allows break-up of connections on one of the gateway paths. This study aims to determine the effect of failover on SDN and conventional networks that are integrated with load balancing method of ECMP on MikroTik RB951-2n router device. The controller used on the SDN network is OpenDaylight. Testing is done by doing failover test which then data of bandwidth traffic from both network architecture recorded using Graphing tool from MikroTik. For average traffic efficiency without failover influence on conventional network better with difference of 9.8%. And with the difference in efficiency of 0.5% menunujukkan that the effect of failover on the SDN network is still better than the conventional network.